«FOLKLORE»: ON THE HISTORY OF THE USE OF TERMS AND ITS IMPORTANCE IN RUSSIAN SCIENCE - Дранникова, Наталья Васильевна; Drannikova, Natalya (Trudy Karelʹskogo nauchnogo t͡s︡entra Rossiĭskoĭ akademii nauk, 2015)
The relevance of the study is that the article contains the overview of the complete history of the term “folklore” in the Russian science throughout the XIX and XX centuries. The instability and inaccuracy of the term the way it was understood in the 1880-1890s were the reason why the Russian scientists seldom used it. In the XIX century the field of folklore included everything which could be referred to the folk knowledge. Having analyzed different viewpoints, we have come to the conclusion that in the Russian folklore studies in the XX century this term had a more narrow meaning than in the foreign folklore studies and meant oral folk arts. Y. M. Sokolov finally legalized such understanding of the word “folklore”. The term became widespread due to the A. M. Gorkiy’s speech made on the First All-Soviet Union Conference of the Soviet Writers. At the turn of the XIX-XX centuries there existed 4 concepts regarding the understanding of folklore (sociological, aesthetic, philological, theoretical-communicative). In the Soviet period of the folklore studies the basic features of folklore are its oral and collective character, but in the later period of studies – its traditional character. The change of the objects and methods of research has taken place in the modern folklore studies, this has led to the changes of the scientific paradigm and to the broadening of the meaning field of the word “folklore”, which now correlates not only with the subject itself, but also with its concept. The objects of the folklore studies now also include the products of modern urban “spontaneous” culture which were not previously scientifically analyzed. The modern folklore studies is focused on speech practices and communication practices. The study of folklore from the perspective of pragmatics is more preferable nowadays.